2000
DOI: 10.1902/jop.2000.71.10.1567
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Age on Proliferating Cell Nuclear Antigen Expression in Oral Gingival Epithelium of Healthy and Inflamed Human Gingiva

Abstract: Our data indicate that PCNA expression in inflamed gingiva is higher in older subjects. Furthermore, a significant correlation was noted between aging and PCNA expression in inflamed gingiva. As there is no increase in mucosal epithelial thickness despite increased proliferation, we speculate that the duration of the PCNA+ phase in cell cycle may be longer in older subjects. This study also implies that PCNA immunolocalization can be used as an index of the state of cell proliferation in both biological and pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 45 publications
4
30
2
Order By: Relevance
“…In this study, we did not find any significantly changed level of PCNA expression in the gingival epithelia of the PED group. In contrast with our findings, some studies suggest the presence of increased PCNA activity in oral gingival epithelium during inflammation (38,41) and Tsuji et al suggested a higher level of PCNA protein in tumors (42). Thus, it becomes apparent that ALA can affect PCNA activity and/ or apoptosis related pathologic conditions in the gingival tissue of periodontitis induced rats.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In this study, we did not find any significantly changed level of PCNA expression in the gingival epithelia of the PED group. In contrast with our findings, some studies suggest the presence of increased PCNA activity in oral gingival epithelium during inflammation (38,41) and Tsuji et al suggested a higher level of PCNA protein in tumors (42). Thus, it becomes apparent that ALA can affect PCNA activity and/ or apoptosis related pathologic conditions in the gingival tissue of periodontitis induced rats.…”
Section: Discussioncontrasting
confidence: 99%
“…In a normal cell cycle, PCNA is a nuclear protein that has an important function in DNA synthesis. PCNA protein level is directly related to cell proliferation and PCNA functions are controlled by p21 CIF1 ⁄ WAF1 , which is also controlled by the p53 gene (33,38,39). The P53 gene contributes to the inhibition of cell growth and can actively arrest the cell cycle and trigger apoptosis (40).…”
Section: Discussionmentioning
confidence: 99%
“…3 H]-thymidine (15,16) and by immunohistochemical detection of markers such as proliferating cell nuclear antigen (PCNA) (17). A few junctional epithelial cells attached to tooth were labeled by incubation for three hours in medium containing [ In contrast, the sulcular and oral gingival epithelia exhibited certain level of proliferative activity as shown in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there is no consensus in the literature on how epithelial maturation and proliferation are affected by age 6,13,15,19,24) . Çelenligil-Nazliel et al 4) did not find differences in epithelial renewal. However, aging is related to a gradual reduction in connective tissue turnover.…”
Section: Introductionmentioning
confidence: 87%